Analisis Pengaruh Rasio Keuangan Terhadap Harga Saham Pada Perusahaan Manufaktur Yang Terdaftar Di Bursa Efek Inonesia Pada Tahun 2009-2013 - Lutfie, Muhammad; , Imron Rosyadi, S.E., M.Si (2015)
This study aimed to analyze the influence of financial ratios (ratio of profitability, liquidity and solvency) on stock prices companies listed on the Stock Exchange the period 2009 to 2013. The population in this study are all companies listed on the Stock Exchange the period 2009 to 2013. While the sample of this company is a manufacturing company that has met certain criteria. Data analysis method used is multiple regression analysis, the data used in the form of financial statements of companies listed on the Indonesia Stock Exchange for the years 2009-2013. Results of the research that has been conducted shows that there is simultaneously a positive and significant influence between the ratio of profitability, liquidity and solvency to the stock price. Further t test results in this study show that ROA significantly influence stock prices with a significance of 0.000 which is smaller than 0.05. As for the variables CR and DER partially no significant effect. Effect of R square in the study by 33% and the remaining 67% can be explained by other factors or other variables outside the model in this study.